COMPARISON AND OPTIMIZATION OF TRANSIENT TRANSFECTION METHODS IN THE HEK293T CELL LINE - Issabekova , A.S.; Zhunusova , M.S.; Ramanculov , E.M.; Kulyyassov , A.T. (Eurasian Journal of Applied Biotechnology, 2017)
The expression of transgenes and control of gene expression in mammalian cells is an active area of biomedical research. Therefore, the improvement of methods for effective gene transfer into eukaryotic cells is of great interest and remains are search priority. We compared different methods of transient transfection of HEK293T cells, namely calcium phosphate with different pH values of the HBS buffer solution,6.90, 6.95, 7.00, 7.05 and 7.10, as well ascommercial sets of FuGENE and Lipofectamine. Results were analyzed using fluorescence microscopy with green fluorescent protein GFP as a reporter gene. We determined that the optimal pH of the HBS phosphate buffer for transient transfection was 6.95. A small pH deviation in the range of 6.90–7.10 did not significantly modify the expression efficiency of a protein of interest. Among the methods studied, Lipofectamine showed the highest level of transfection efficiency based on expression of the GFP protein, but exceeding the recommended dose of this reagent exerted a toxic effect on the viability of HEK293T cells.